Christen Dalsgaard som grundtvigsk billedkunstner - Hobolth, Nina (Grundtvig-studier, 2001)
Christen Dalsgaard as a Grundtvigian Pictorial Artist By Nina Hobolth The article elucidates the connection between the first generation of Grundtvig’s disciples and the painter Christen Dalsgaard (1824-1906). This connection derives from the close bonds between people who play an important role in the creation of pictorial art, but who are very often not given the appropriate attention by art history.In Dalsgaard’s case, such connections go as far back as to his childhood and youth among the revivalist circles in the Salling-Mors region, which developed into a strong Grundtvigian movement, and the ties were strengthened during his work as a drawing master at Sorø Akademi. Nina Hobolth presents three examples of Dalsgaard’s work as a Grundtvigian painter. First the altarpiece in the church of the valgmenighed (i.e. a congregation within the Established Church, claiming the right to choose their own clergyman) at Ryslinge from 1869 is examined. The motif here is the Holy Family in Nazareth, presented as an .ordinary. family with God’s word in their midst. Thus the altarpiece functions as a symbol of the mid-Funen families, whose Christian life in home and congregation was the basis of their valgmenighed. The Grundtvigian emphasis on the importance of baptism is pointed out by the fact that Jesus has his arm round a font.The altarpiece in the church of the valgmenighed - today a frimenighed (i.e. an independent congregation, outside the Established Church) - on Mors, the Ansgar Church, was commissioned and donated by the lay preacher Peder Larsen Skr.ppenborg in 1871-1872, and represents Ansgar baptizing the first Danish child in the Helligbcek near Hedeby. The motif combines, in a Grundtvigian sense, Christianity, folkelighed, and history in a way probably unheard of so far in Danish church decoration, Ansgar becoming the symbol of Danish Christianity. The connection with Grundtvig’s church view is further emphasized by the fact that baptism has been chosen as the central motif. Thus, along with the Communion table, Christ’s presence at Baptism and Communion is emphasized. The fact that it is not a moralizing motif, but one that serves to strengthen the congregational community adds a light touch to the message of the altarpiece. In 1876 Folk High School Principal Ernst Trier wanted a repetition of the motif for a decoration of the extended lecture hall at Vallekilde Folk High School, the picture being intended to function as a Christian and folkelig symbol of revival, depicting the meeting between the Danish people and God’s congregation, the folkelig and the Christian.In conclusion, it is made clear in what way Christen Dalsgaard can be characterized as a Grundtvigian painter: Dalsgaard kept his official artistic career as a genre painter apart from his religious art, which, by virtue of a specific set of basic motifs, confirmed the community of the congregation and the shared values within the Grundtvigian movement. According to the art historian Julius Lange, it is the distinctive ark of Dalsgaard that he masters the psychological expression, and this evaluation was shared by the contemporary Grundtvigian circles who saw Dalsgaard’s pictures as soul-stirring, rendering the »human« content of the motif. His art did not involve any stylistic renewal; such a renewal came about with the painters of the next generation, of whom Joakim Skovgaard in particular caused dismay and admiration.